Drought and salt stress mitigation in crop plants using stress-tolerant auxin-producing endophytic bacteria: a futuristic approach towards sustainable agriculture - Mal, Sadananda; Panchal, Shweta (Frontiers in Plant Science, 2024)
Abiotic stresses, especially drought stress and salt stress in crop plants are accelerating due to climate change. The combined impact of drought and salt is anticipated to lead to the loss of up to 50 % of arable land globally, resulting in diminished growth and substantial yield losses threatening food security. Addressing the challenges, agriculture through sustainable practices emerges as a potential solution to achieve Zero Hunger, one of the sustainable development goals set by the IUCN. Plants deploy a myriad of mechanisms to effectively address drought and salt stress with phytohormones playing pivotal roles as crucial signaling molecules for stress tolerance. The phytohormone auxin, particularly indole acetic acid (IAA) emerges as a paramount regulator integral to numerous aspects of plant growth and development. During both drought and salt stress conditions, auxin plays crucial roles for tolerance, but stress-induced processes lead to decreased levels of endogenous free auxin in the plant, leading to an urgent need for auxin production. With an aim to augment this auxin deficiency, several researchers have extensively investigated auxin production, particularly IAA by plant-associated microorganisms, including endophytic bacteria. These endophytic bacteria have been introduced into various crop plants subjected to drought or salt stress and potential isolates promoting plant growth have been identified. However, post-identification, essential studies on translational research to advance these potential isolates from the laboratory to the field are lacking. This review aims to offer an overview of stress tolerant auxin-producing endophytic bacterial isolates while identifying research gaps that need to be fulfilled to utilize this knowledge for the formulation of crop-specific and stress-specific endophyte bioinoculants to the plant to cope with auxin imbalance occurring during these stress conditions..